Lakes as Natural Tourism Object in North Sulawesi - Kambey, Henny Johanna; Djati, M. Sasmito (Graduate School, Universitas Brawijaya, 2016)
Lake is one of the important natural resources in north Sulawesi and many lakes ecosystem in this province has been used and involved in tourism industry. The aims of the research is to describes the recent status of lakes in North Sulawesi and describes its opportunities for tourism development. The analysis was based on the secondary data and direct field observation. Four lakes, namely Tondano, Pangolombian, Linow and Tampusu have been used as tourism attraction in various degreed. The most intensive used was Lake Tondano, while Lake Linow recently grows as one of the favorites object. Lake Pangolombian and Tampusu receive few tourist visitations. The development of four lakes as tourism object will increase the attractiveness of North Sulawesi as ecotourism development. In such a case, the conservation of lakes becomes crucial. Keywords: economy development, Lake tourism, North Sulawesi.